The National Origins of Policy Ideas : Knowledge Regimes in the United States, France, Germany, and Denmark - Campbell, John L.; Pedersen, Ove K. (Book collections on Project MUSE., 2014)
In politics, ideas matter. They provide the foundation for economic policymaking, which in turn shapes what is possible in domestic and international politics. Yet until now, little attention has been paid to how these ideas are produced and disseminated, and how this process varies between countries. The National Origins of Policy Ideas provides the first comparative analysis of how "knowledge regimes"--Communities of policy research organizations like think tanks, political party foundations, ad hoc commissions, and state research offices, and the institutions that govern them--generate ideas and communicate them to policymakers. John Campbell and Ove Pedersen examine how knowledge regimes are organized, operate, and have changed over the last thirty years in the United States, France, Germany, and Denmark. They show how there are persistent national differences in how policy ideas are produced. Some countries do so in contentious, politically partisan ways, while others are cooperative and consensus oriented. They find that while knowledge regimes have adopted some common practices since the 1970s, tendencies toward convergence have been limited and outcomes have been heavily shaped by national contexts. Drawing on extensive interviews with top officials at leading policy research organizations, this book demonstrates why knowledge regimes are as important to capitalism as the state and the firm, and sheds new light on debates about the effects of globalization, the rise of neoliberalism, and the orientation of comparative political economy in political science and sociology.